Case Study : Dystocia on Beef Cattle in Kunir Regency of Lumajang District, East Java, Indonesia in 2015 and 2016 - Febrianila, Rosiana; Lokapirnasari, Widya P; Restiadi, Tjuk I; Mustofa, Imam; Hermadi, Herry A; Safitri, Erma (KnE Life Sciences, 2017)
Dystocia defined as difficulty of birth. Cattle that experienced dystocia characterized by extended processing time of birth, difficult, and impossible to do without help of human stem. This study aimed to determine the number and causative factor of dystocia in beef cattle in Kunir sub district, Lumajang district. Data acquisition used primary data and secondary data. Primary data was obtained from direct observations about management of maintenance, then interviewed the farmers in Kunir sub district. Secondary data was data obtained from the recording belongs to animal health technical officer. The results showed that the prevalence of dystocia in Kunir district, Lumajang district as many as 63 cases or 11,6 % of 543 births. The result of the research is analyzed using chi square (χ2) method on SPSS 20.0 program and risk factors that increase the incident of dystocia were IB semen which greater than the cattle site, the position of the fetus and inertia uteri can result in weakness of the catrle at the age of older and more likely to give birth. Key words: Dystocia; beef catlle